(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
The problems encountered during teaching Turkish to Macedonian students whose mother tongue is Macedonian were addressed, and the information in this study, in which solutions were offered on what to do in the face of these problems, was obtained by participating in the observation method, through classroom practices and by evaluating written exams. Evaluations were obtained from three groups. The number of students in these groups is thirty-five. The age range of these learners is between eighteen and forty years. The mistakes made have been written down. The desire to learn Turkish is supported by different reasons such as Turkish TV series, Turkish songs, the desire to go on holiday to Turkey and speak Turkish with the Turks, and the friendliness of the Turks. Turkish is the language of a strategically important country at the intersection of Europe and Asia. Keywords: Teaching Turkish to foreigners; problems in teaching Turkish; vowels; consonants.